Preliminary study on the fabrication of aluminium foam through pressure assisted sintering dissolution process - Mustapha, Mazli; Mamat, Othman; Hussain, P (ELSEVIER, 2010)
This paper presents the work carried out to develop a technique based on pressure assisted sintering dissolution process (PASDP) to produce open celled aluminium foam. In contrast to metallic foams made by solid state sintering dissolution process (SSSDP), aluminium foams made by this improved technique has high dense of cell wall which can be attained in a much shorter time and possess superior mechanical properties. By varying the local sodium chloride (NaCl) volume fractions in the sodium chloride/aluminium (NaCl/Al) perform, it is possible to fabricate aluminium foam with different relative densities. The fabricated aluminium foam also exhibits typical stress-strain behaviour of metallic foam when subjected to monotonic compression mode. The principles of Taguchi’s Design of Experiments were employed to optimize processing factors for the fabrication of aluminium foam. Results were analysed based on Taguchi’s signal to noise ratio (S/N) and analysis of variance (ANOVA) techniques in order to obtain the optimum combination of process parameter settings. Results indicate that the most notable factor influencing the fabrication of Al foam was the compaction at elevated temperature, followed by temperature, time and the process heating rate. The optimum processing parameters for the PASDP process was then predicted based on these results.